Exposure and post-exposure effects of chlorpyrifos on Carassius auratus gills: An ultrastructural and morphofunctional investigation. (July 2020) - Macirella, Rachele; Madeo, Giuseppe; Sesti, Settimio; Tripepi, Manuela; Bernabò, Ilaria; Godbert, Nicolas; La Russa, Daniele; Brunelli, Elvira
Abstract: Widespread environmental contamination from chlorpyrifos (CPF) is well acknowledged and has led to the proposal to ban or limit its use in agricultural and domestic, within the regulatory context of both America and Europe. Furthermore, great concerns arise as to whether exposure to CPF represents a potential risk to human health. In the present study, by subjecting the goldfish model to three environmentally realistic concentrations of CPF (1, 4, and 8 μg/L) for 96 h, we demonstrated that this pesticide has the potential to induce severe morphological, ultrastructural and functional alterations in gills, even at very low concentrations. The degree of pathological effects was dose-dependent, and the main morphological alterations recorded were: regression of interlamellar cellular mass (ILCM), hypertrophy, and hyperplasia of epithelial cells, degeneration of both chloride cells and pillar cells. CPF exposure resulted in a decrease of Na + /K + -ATPase expression and the induction of iNOS, as revealed by immunohistochemical analysis. In order to determine the overall toxicity of CPF, we also investigated the recovery capability of goldfish gills following a period of 7 days in pesticide-free water. Our results clearly showed that there exists a threshold of CPF dose below which the effects on gills are reversible and beyond which the ability of gills to recover their typical features is completely lost. The information presented in this paper emphasises the importance of evaluating the recovery ability of organisms after chemical input and enhances our knowledge of the potential hazard of organophosphorus pesticides (OPs) on freshwater ecosystems. Graphical abstract: Image 1 Highlights: After short-term exposure dose-dependent morphofunctional alterations were observed. There exists a threshold of CPF dose beyond which the effects are not-reversible. CPF affect gills function through Na + /k + -ATPase downregulation. iNOS is differentially expressed in gills after exposure and post-exposure period.